2023
DOI: 10.1182/bloodadvances.2022009236
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-rich glycoprotein attenuates catheter thrombosis

Abstract: Factor (F) XII knockdown attenuates catheter thrombosis in rabbits. Because histidine-rich glycoprotein (HRG) modulates FXIIa activity, we hypothesized that HRG depletion would promote catheter thrombosis. To test this, rabbits were given antisense oligonucleotides (ASOs) against HRG, FXII, or a control ASO or saline. The activated partial thromboplastin time (aPTT), prothrombin time (PT), and catheter-induced thrombin generation were determined in blood collected before and after treatment. Compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…25 Second, HRG binds FXIIa (activated FXII) and attenuates its capacity to promote autoactivation and to activate FXI. [25][26][27] The relative importance of these 2 mechanisms is uncertain.…”
Section: See Accompanying Editorial On Page 1671mentioning
confidence: 99%
“…25 Second, HRG binds FXIIa (activated FXII) and attenuates its capacity to promote autoactivation and to activate FXI. [25][26][27] The relative importance of these 2 mechanisms is uncertain.…”
Section: See Accompanying Editorial On Page 1671mentioning
confidence: 99%
“…In this issue of Blood Advances , Malik et al have shown that plasma concentrations of histidine-rich glycoprotein (HRG) modulate factor XIIa (FXIIa) activity and, in turn, catheter thrombosis. 1 This observation suggests that high concentrations of HRG may reduce contact activation and, thus, thrombosis. These studies may be the first step toward characterizing and translating a target that reduces thrombosis risk without affecting hemostasis.…”
mentioning
confidence: 98%
“…This background set the stage for the investigations of this article. 1 In these studies, Malik et al questioned whether HRG depletion would promote catheter thrombosis. It is generally agreed that FXII is the major promoter of catheter thrombosis because its knockdown attenuates it.…”
mentioning
confidence: 99%